CARACTERIZAÇÃO MICROESTRUTURAL DAS PARTÍCULAS DE SEGUNDA FASE DE UMA LIGA DE ALUMÍNIO AA7050 NAS CONDIÇÕES T7451, T6 E T6I4-65 - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The AA7050 class from the 7XXX series alloys based on Al-Zn-Mg-Cu are widely used in aerospace structures and fuselage components, when the same are subjected to high stress loading due to its high ratio mechanical strength to density, in addition, to its corrosion resistance. The increased resistance of these alloys is obtained by heat treatment that involves solution treatment and ageing followed precipitation of a fine and homogeneous phase from the own chemical composition. In this, the present study aimed to perform the of AA7050 aluminum alloy microstructural characterization with different ageing heat treatment from the T7451, T6 and T6I4-65 conditions. Thus, different characterization techniques from the Optical Microscopy (OM), Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Extraction of second phase particles, X-ray Diffraction (XRD) and Transmission Electron Microscopy (TEM) were used. It was evaluated which condition results is higher precipitation hardening phases that are responsible for the increased resistance of the alloy. The most significant results were obtained by TEM where it was possible to determine the morphology of the GPII zones in needles form with approximate size of 30nm and 10nm for both T6 and T6I4-65 conditions, respectively. Moreover, the metastable η' phase was identified in platelets form in the T7451, T6 and T6I4-65 conditions with approximate size of 50nm, 20nm and 10nm, respectively. The surface roughness analyses obtained by AFM have revealed that the T6I4-65 condition has higher surface roughness (Ra=14,87nm) when compared to the T7451 (Ra=7,65nm) and T6 (Ra=8,35nm) conditions. Indicating in this case, a higher density of small particles homogeneously distributed in the T6I4-65 aluminum alloy matrix.
CARACTERIZAÇÃO MICROESTRUTURAL DAS PARTÍCULAS DE SEGUNDA FASE DE UMA LIGA DE ALUMÍNIO AA7050 NAS CONDIÇÕES T7451, T6 E T6I4-65
Keywords: alumínio AA7050; precipitação secundária; envelhecimento interrompido; AA7050 aluminum alloy; secondary precipitation; interrupted ageing; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA